Mali Financial Sector Assessment Program : The Banking System and Credit to the Economy - World Bank (World Bank, Washington, DC, 2016)
There has been significant development of Mali’s banking sector in recent years, but it remains shallow, and access to banking services is limited. With the opening of a new bank in 2014, there are now 14 commercial banks operating in Mali. There has been a positive evolution of the banking sector in Mali from 2009-13. There have been a number of changes in recent years in the ownership structure of the banking sector, which is now dominated by foreign shareholders, primarily from Africa. The emergence of WAEMU banking groups is a recent phenomenon, spurred in part by the approval of a single banking license for the sub-region. Available financial soundness indicators (FSI) suggest that the banking sector is generally sound, though performance varies widely among banks, and asset quality is weak.